Context, Cognition, and Communication: Understanding how the Psychology of Location Affects Health and Medical Communication - Amant, Kirk St. (European Scientific Journal, ESJ, 2021)
Prior research reveals that cognition – or how the mind processes information – often guides human behavior in familiar settings (St.Amant, 2018). Such factors can affect the communication practices persons use to convey information about health concepts or medical processes (Hamm, 2003; St.Amant, 2021). The challenge becomes anticipating such connections in order to create texts and visuals audiences can understand and use to meet healthcare needs. This article presents an approach to meeting this need by applying the concept of cognitive scripts to understand and address the communication expectations audiences often associated with health and medical settings. In presenting these ideas, the article begins with an explanation of how cognitive scripts can affect communication processes. From there, the author advocates applying script dynamics to health and medical communication practices. To do so, the author expands upon ideas in the literature on cognitive scripts to create a script-based approach for researching an audience’s expectations of healthcare situations. The author then describes how to apply the information collected from this research to create communication materials audiences can more easily use in healthcare contexts. The result is a three-factor method that focuses on applying cognitive scripts to identify and address an audience’s expectations for healthcare communication in a given context. Readers can then use this approach to design healthcare communication materials that audiences can easily and effectively use.